Improved Brain MR Imaging from a Compact, Lightweight 3T Scanner with High‐Performance Gradients. Issue 1 (28th June 2021) - Camerucci, Emanuele; Campeau, Norbert G.; Trzasko, Joshua D.; Gray, Erin M.; Bernstein, Matt A.; Cogswell, Petrice M.; Shu, Yunhong; Foo, Thomas K.; Huston, John
Abstract : Background: A low‐cryogen, compact  3T (C3T) MRI scanner with high‐performance gradients capable of simultaneously achieving 80 mT/m gradient amplitude and 700 T/m/second slew rate has been in use to study research patients since March 2016 but has not been implemented in the clinical practice. Purpose: To compare head MRI examinations obtained with the C3T system and a conventional whole‐body  3T (WB3T) scanner in seven parameters across five commonly used brain imaging sequences. Study Type: Prospective. Subjects: Thirty patients with a clinically indicated head MRI. Sequence:  3T; T1 FLAIR, T1 MP‐RAGE, 3D T2 FLAIR, T2 FSE, and DWI. Assessment: All patients tolerated the scans well. Three board‐certified neuroradiologists scored the comparative quality of C3T and WB3T images in blinded fashion using a five‐point Likert scale in terms of: signal‐to‐noise ratio, lesion conspicuity, motion artifact, gray/white matter contrast, cerebellar folia, susceptibility artifact, and overall quality. Statistical Test: Left‐sided, right‐sided, and two‐sided Wilcoxon signed rank test; Fisher's method. A P value <0.05 was considered statistically significant. Results: The C3T system performed better than the WB3T in virtually all comparisons, except for motion artifacts for the T1 FLAIR and T1 MP‐RAGE sequences, where the WB3T system was deemed better. When combining all sequences together, the C3T system outperformed the WB3T system in all image quality parameters evaluated, except for motion artifact ( P  = 0.13). Data Conclusion: The C3T scanner provided better overall image quality for all sequences, and performed better in all individual categories, except for motion artifact on the T1 FLAIR and T1 MP‐RAGE. Level of Evidence: 2 Technical Efficacy Stage: 1